Pharmacoperone rescue of vasopressin 2 receptor mutants reveals unexpected constitutive activity and coupling bias - Janovick, Jo Ann (PLoS One, 2017)
Pharmacoperones are small molecules that diffuse into cells and rescue misfolded, mistrafficked protein mutants, restoring their function. These substances act with high target specificity, serving as templates to fold (or refold) receptors, enzymes, ion channels or other proteins and enable them to pass the scrutiny of the cellular quality control system (“rescue”). In the present study we demonstrate that a rescued mutant (L83Q) of the vasopressin type 2 receptor (V2R), shows a strong bias for Gs coupling unlike the WT V2 receptor, which couples to both Gs and Gq/11. Failure of the mutant to couple to Gq/11 was not due to a limiting quantity of G-proteins since other Gq/11-coupled receptors (WT V2R, histamine receptor and muscarinic receptor) responded appropriately to their ligands. Transfection with DNA encoding Gq enabled the V2 receptor mutant to couple to this G protein, but only modestly compared with the WT receptor. Fourteen V2R mutant pharmacoperones, of multiple chemical classes, obtained from a high throughput screen of a 660,000 structure library, and one V2R peptidomimetic antagonist rescues L83Q. The rescued mutant shows similar bias with all pharmacoperones identified, suggesting that the bias is intrinsic to the mutant protein’s structure, rather than due to the chemical class of the pharmacoperone. In the case of V2R mutant Y128S, rescue with a pharmacoperone revealed constitutive activity, also with bias for Gs, although both IP and cAMP were produced in response to agonist. These results suggest that particular rescued receptor mutants show functional characteristics that differ from the WT receptor; a finding that may be important to consider as pharmacoperones are developed as therapeutic agents.